Estimating the capacity of the Ethereum platform based on the mathematical model of the smart contract - Ivanov, М.; Oliynykov, R. (Radiotekhnika, 2017)
A mathematical model for smart contracts for deployment of the initial coin offering (ICO), widely used on the Ethereum platform, is proposed. The analysis of dependence of the network capacity on such parameters as the transaction buffer size, the average transaction processing time, is performed. Evaluations are obtained of which parameters have the greatest impact on the capacity of Ethereum within the developed model.